An Enzymatic Toolbox for Cascade Reactions: A Showcase for an In Vivo Redox Sequence in Asymmetric Synthesis. Issue 12 (13th September 2013) - Oberleitner, Nikolin; Peters, Christin; Muschiol, Jan; Kadow, Maria; Saß, Stefan; Bayer, Thomas; Schaaf, Patricia; Iqbal, Naseem; Rudroff, Florian; Mihovilovic, Marko D.; Bornscheuer, Uwe T.
<x xml:space="preserve">Abstract</x> Joined forces: Alcohol dehydrogenase, enoate reductase, and Baeyer–Villiger monooxygenase are combined in a cascade reaction by coexpression in E. coli to have a recombinant whole‐cell biocatalyst. Such an artificial metabolic "mini"‐pathway provides access to functionalized chiral compounds in high yields and optical purities as exemplified for kinetic resolutions, desymmetrizations, and regiodivergent biotransformations.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>